PENDIDIKAN ISLAM PADA MASA DAULAH USMANI (Sejak Sultan Mahmud II Sampai Menjadi Negara Turki Modern oleh Mustafa Kemal) - H. Halim K (IAIN PAREPARE, 2016)
This paper raised the dynamic development of Islamic education at the time of the Ottoman Daulah using literature review approach. In this paper reveal the characteristics of Islamic education in Daulah Ottoman period that begins by describing the history Daulah since the Ottoman Sultan Mahmud II until the time of Mustafa Kemal. The existence of Islamic education during this Daulah have ups and downs as a consequence of the policy pursued by the authorities at the time. But at the time of Mustafa Kemal reforms in government and bring Turkey into the modern era. It also impacts on the development of Islamic education significantly.